Gender implications in sex education, knowledge, and vulnerability to sexually transmitted infections of healthcare students (Research, Society and Development, 2021)
The challenges posed by the implementation of sex education within a social context, by teachers or parents, are impasses that compromise adolescents’ and young adults’ sexual health, resulting in sexual risk behaviors. This study evaluated the forms of sex education, knowledge about sexually transmitted infections, and the vulnerability of university students within the Brazilian Legal Amazon. A total of 149 healthcare students provided their sociodemographic data and how they obtain information about safe sex practices. The data collected were evaluated using the Sexually Transmitted Disease Knowledge Questionnaire (STD-KQ) questionnaire. Bivariate analyses and Pearson correlation were performed. The sources of sex education were primarily accessed by students approaching course completion and female students nearing graduation, through teachers, specialized books, media, and friends. In general, men were found to have a higher degree of knowledge about STIs, while women reported feeling less protected sexually. Time spent at the university and the knowledge men possess were not found to reduce risky behavior. This cross-sectional study confirms that interventions to combat misinformation in the face of risky sexual behaviors and their consequences should be prioritized and should consider the gender of individuals and all the differences in the perceptions and actions of both male and female healthcare students.